Implementasi Protokol Anchor-Based Street and Traffic Aware Routing (A-Star) menggunakan Intersection Node pada Vehicular Ad-Hoc Network (VANET) - Danny Candra Rumantyo; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Vehicular Ad-Hoc Network (VANET) is a wireless network technology that supports vehicle communication. The problems and research focus on VANET are generally related to the selection of effective routing protocols. Topology-based protocols in the Mobile Ad-Hoc Network (MANET) still have limitations because they are vulnerable to fast node movement and dynamic topology changes but are still used on VANET. Position-based protocol removes these limitations, so it is the most appropriate protocol used in the VANET environment. In this study the routing protocol used is Anchor-Based Street and Traffic Aware Routing (A-STAR). The A-STAR protocol is included in the position-based protocol category and has a mechanism of action based on intersections on the road. This study uses Simulation of Urban Mobility (SUMO) and Network Simulator 3 (NS-3) to simulate the A-STAR protocol based on a real map. The test scenario that will be used to test the protocol is the number of nodes, node speed, and the number of node intersections. The results of the test are analysis metrics consisting of packet delivery ratio, end-to-end delay, routing overhead, convergence time, and euclidean distance. The test results of the three scenarios show the average value of packet delivery ratio of 85.1%, end-to-end delay of 93.28ms, routing overhead of 873.88 packets, convergence time of 1.46s, and euclidean distances of 104 , 64m.